Use of p30,pK205R and pB602L recombinant proteins for African swine fever serodiagnosis - M. R. Yakupov; A. S. Yakovleva; A. V. Scherbakov (Ветеринария сегодня)
P30, pK205R and pB602L recombinant proteins of African swine fever (ASF) virus were generated by expression in £ coli. Indirect ELISA for detection of antibodies to ASF virus was developed on the base of the said recombinant proteins. Diagnostic specificity of pK205R-and pB602L-ELISA tests systems was 99,8%, рЗО-ELISA - 99,5%. Diagnostic sensitivity p30-ELISA/pK205R-ELISA and pB602L-ELISA was 100% and 94,12%, respectively, when the reference panel of positive sera was used. The sensitivity рЗО-ELIS A and pK205R-ELIS A used for testing sera from experimentally and naturally infected animals was found to be higher than that one of commercial test systems and comparable to the ELISA recommended by the World Animal Health Organization for ASF serological diagnosis. High рЗО-ELISA and pK205R-ELISA specificity and sensitivity were confirmed by results of international proficiency testings for ASF diagnosis.